Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fneur.2018.00974
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Stroke and Hypoperfusion in Patients With Isolated Vertigo and Vascular Risk Factors

Abstract: Background and Purpose: The aim of this study was to determine the prevalence and associated factors of stroke and hypoperfusion among patients with isolated vertigo and vascular risk factors.Methods: We studied 157 patients with isolated vertigo who had undergone multimodal magnetic resonance imaging. Magnetic resonance angiography (MRA) was used to measure the diameters of vertebrobasilar arteries and to evaluate morphologic changes to vessels. Measurements obtained included length of the basilar artery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…In this chronic process, VAH seemed to be the consequence of the interaction between the unequal VA flow and the basilar artery curvature, or just acted as an initial factor ( 16 ). A hypoplastic VA can also result in the ipsilateral occlusion of this vessel due to a direct decrease in blood flow and easy collapse of the vessel caused by the smaller intracranial VA caliber ( 17 ). A hypoplastic VA can cause ipsilateral posterior inferior cerebellar artery infarction by directly decreasing the blood flow in the smaller intracranial VA ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this chronic process, VAH seemed to be the consequence of the interaction between the unequal VA flow and the basilar artery curvature, or just acted as an initial factor ( 16 ). A hypoplastic VA can also result in the ipsilateral occlusion of this vessel due to a direct decrease in blood flow and easy collapse of the vessel caused by the smaller intracranial VA caliber ( 17 ). A hypoplastic VA can cause ipsilateral posterior inferior cerebellar artery infarction by directly decreasing the blood flow in the smaller intracranial VA ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical spectrum of cerebellar strokes rarely presents with isolated dizziness or without clear central neurological deficits (e.g., dysarthria or ataxia). Sometimes, isolated acute labyrinthine damage may herald impending pontocerebellar involvement in infarction in the territory of the anterior inferior cerebellar artery and may cause brainstem or cerebellar strokes; vestibular strokes are often overlooked because they mimic more benign hearing disorders [ 24 , 63 ]. Lee et al [ 64 ] and Deng et al [ 65 ] found that vestibular structures were more vulnerable to ischemia than any other structures in the brainstem and cerebellum, with the medial vestibular nucleus being the most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of extracranial arterial stenosis was defined as artery stenosis >50% ( 13 ). Smoker was defined as continuous or cumulative history of smoking >9 months and ≥1 cigarette per day ( 14 ). Alcohol consumption during the past 3 months was also recorded (the standard alcohol consumption criteria is equivalent to 300 ml of beer or 100 ml of wine).…”
Section: Methodsmentioning
confidence: 99%